AN EFFECTIVE USAGE OF DUAL CURRENT MIRROR BASED VOLTAGE LEVEL SHIFTER (International Journal of Food and Nutritional Sciences, 2022)
Voltage level shifters play a crucial role in modern integrated circuit design, facilitating seamless communication between digital blocks operating at different voltage domains. This abstract introduces a novel Voltage Level Shifter architecture featuring a Dual Current Mirror configuration. The proposed Voltage Level Shifter leverages the benefits of dual current mirrors to achieve high-performance voltage level shifting while minimizing power consumption and area overhead. By employing a dual-current mirror setup, the design ensures efficient and reliable signal propagation between distinct voltage domains, a critical requirement for mixed-signal and multi-voltage integrated circuits. This paper presents a comprehensive analysis of the design, including theoretical underpinnings, simulation results, and practical implementation considerations. The dual current mirror configuration not only enhances signal integrity but also minimizes voltage drop, ensuring minimal distortion during the level shifting process. Furthermore, the proposed Voltage Level Shifter demonstrates superior performance in terms of speed, power efficiency, and robustness, making it a compelling choice for a wide range of applications, from energy efficient IoT devices to high-performance computing systems. The presented design represents a significant advancement in voltage level shifting techniques, offering a versatile and efficient solution for today's diverse and demanding integrated circuit requirements.